Tingkat Stres dan Mekanisme Koping Remaja Di Lapas: Indonesia - Ardi, Velisia Dwi Puspita; Zukhra, Ririn Muthia; Agrina, Agrina (Jurnal Kesehatan Holistic, 2022)
Adolescentss tend to do deviant actions such as juvenile delinquency so that adolescentss have to deal with the law. Adolescentss who are in the Child Special Guidance Institute (LPKA) experience life changes and make adolescentss experience stress. Stress can be overcome with effective coping mechanisms from adolescents in LPKA. This study aims to describe the stress level and coping mechanisms of adolescents at the Class II Special Guidance Institute for Children in Pekanbaru. This study uses a simple descriptive design. The number of respondents was 45 juvenile detainees using accidental sampling technique. The inclusion criteria of sample is adolescents in LPKA around have 12-18 years old and the elxclusion criteria is adolescents have aged more than 18 years old. The analysis used is univariate analysis. The questionnaires used in this study were DASS (Depression Anxiety and Stress Scale) and Brief Cope. The validity test of the DASS questionnaire is 0,48-0,68 dan the reliability value is 0,90. The validity value of the COPE brief questionnaire is 0,447-0,640 and the reliable value is 0,909. The results showed that the majority of the characteristics of the respondents were adolescentss who were in the middle age (15-17 years) as many as 24 respondents (53.3%), and the case of adolescentss in LPKA namely theft as many as 15 respondents (33.3%). The stress level of respondents who had the highest presentation was moderate stress as many as 17 respondents (37.8%) and the coping mechanism of respondents who had the largest presentation was a coping mechanism that focused on emotions as many as 23 respondents (55.6%). Overall, juvenile detainees had moderate stress levels and emotional-focused coping mechanisms